2022
DOI: 10.4239/wjd.v13.i4.319
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive disorder and dementia in type 2 diabetes mellitus

Abstract: Insulin, a key pleiotropic hormone, regulates metabolism through several signaling pathways in target tissues including skeletal muscle, liver, and brain. In the brain, insulin modulates learning and memory, and impaired insulin signaling is associated with metabolic dysregulation and neurodegenerative diseases. At the receptor level, in aging and Alzheimer’s disease (AD) models, the amount of insulin receptors and their functions are decreased. Clinical and animal model studies suggest that memory improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 88 publications
0
27
0
Order By: Relevance
“…A meta-analysis confirmed that the incidence of MCI in patients with T2DM was approximately 45.0% (95% CI = 36.0, 54.0) ( You et al, 2021 ). Multiple pieces of evidence have indicated that T2DM is related to vascular dementia (VD) and Alzheimer’s disease (AD) ( Chau et al, 2020 ; Lyu et al, 2020 ; Ortiz et al, 2022 ). Recent studies have revealed that older patients with T2DM have a higher risk of MCI or dementia, compared to young patients with a similar condition ( Sanke et al, 2014 ; Gao et al, 2016 ; Machii et al, 2020 ; Suain Bon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis confirmed that the incidence of MCI in patients with T2DM was approximately 45.0% (95% CI = 36.0, 54.0) ( You et al, 2021 ). Multiple pieces of evidence have indicated that T2DM is related to vascular dementia (VD) and Alzheimer’s disease (AD) ( Chau et al, 2020 ; Lyu et al, 2020 ; Ortiz et al, 2022 ). Recent studies have revealed that older patients with T2DM have a higher risk of MCI or dementia, compared to young patients with a similar condition ( Sanke et al, 2014 ; Gao et al, 2016 ; Machii et al, 2020 ; Suain Bon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HGD diet is rich in sucrose and was chosen since sucrose has a high glycemic index, and compared to LGD, the quantity of sucrose is double. A diet based on sucrose enrichment has been well studied in the context of neurodegenerative brain diseases such as Alzheimer’s disease [ 91 ], of interest to our work, and sucrose can be responsible for cognitive disorders and dementia [ 92 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the significance of the link between T2D and AD is now defined by the term “type 3 diabetes”, which describes a subset of diabetic patients who develop AD dementia [ 117 119 ]. In T2D, insulin resistance and altered IGF-1/IGF-1R signaling are associated with cognitive decline, Aβ production, tau hyperphosphorylation, proinflammatory marker’s expression, oxidative stress, and dyslipidemia [ 120 , 121 ]. Rui-Hua et al found that decreased serum IGF-1 levels were associated with T2D-associated cognitive decline in clinical trials [ 122 ].…”
Section: Metabolic Syndrome and Neuropathologymentioning
confidence: 99%